Ethnic minorities in Europe as a legal and political problem? - Korybut Woroniecki, Aleksander (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the issue of national minorities in Europe at the turn of the twentieth and twenty-first centuries, examining whether its essence is primarily legal or political in nature. The author begins with the observation that, following the collapse of the communist system, ethnic conflicts once again became one of Europe’s most significant challenges, with the disintegration of Yugoslavia serving as the most dramatic example. Using a historical-political approach, the study presents the evolution of attitudes toward minority issues from the nineteenth century, through the League of Nations minority protection system, to contemporary European solutions. The author demonstrates that the mere existence of legal regulations is insufficient to resolve ethnic conflicts if there is no political will to implement them. Particular attention is devoted to the tension between the principle of the nation-state and the right of ethnic groups to preserve their own identity. The conclusions indicate that effective minority protection requires both legal instruments and responsible policies pursued by states and international organizations.